Conditional nonparametric frontier models for convex and non convex technologies: A unifying approach - Cinzia Daraio; Leopold Simar (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2005)
The explanation of productivity differentials is very important to identify the economic conditions that create inefficiency and to improve managerial performance. In literature two main approaches have been developed: one-stage approaches and two-stage approaches. Daraio and Simar (2003) propose a full nonparametric methodology based on conditional FDH and conditional order-m frontiers without any convexity assumption on the technology. On the one hand, convexity has always been assumed in mainstream production theory and general equilibrium. On the other hand, in many empirical applications, the convexity assumption can be reasonable and sometimes natural. Leading by these considerations, in this paper we propose a unifying approach to introduce external-environmental variables in nonparametric frontier models for convex and non convex technologies. Developing further the work done in Daraio and Simar (2003) we introduce a conditional DEA estimator, i.e., an estimator of production frontier of DEA type conditioned to some external-environmental variables which are neither inputs nor outputs under the control of the producer. A robust version of this conditional estimator is also proposed. These various measures of efficiency provide also indicators of convexity. Illustrations through simulated and real data (mutual funds) examples are reported.
Keywords: C13; C14; D20; 330; convexity; external-environmental factors; production frontier; nonparametric estimation; robust estimation; Nichtparametrisches Verfahren; Produktivität; Data-Envelopment-Analyse; Theorie